(untitled) (Journal of Applied Oral Science, 2013)
Objective: This study evaluated the effect of temperature and curing time on composite sorption and solubility. Material and Methods: Seventy five specimens (8×2 mm) were prepared using a commercial composite resin (ICE, SDI). Three temperatures (10°C, 25°C and 60°C) and five curing times (5 s, 10 s, 20 s, 40 s and 60 s) were evaluated. The specimens were weighed on an analytical balance three times: A: before storage (M1); B: 7 days after storage (M2); C: 7 days after storage plus 1 day of drying (M3). The storage solution consisted of 75% alcohol/25% water. Sorption and solubility were calculated using these three weights and specimen dimensions. The data were analyzed using the Kruskal-Wallis and Mann-Whitney U Tests (α=5%). Results: The results showed that time, temperature and their interaction influenced the sorption and solubility of the composite (p